Impact of a long-term mentorship program for childbirth providers on quality of care: A cluster randomized controlled trial - Lujia Zhang; Rajet Vatsa; Wei Chang; Sharon Akinyi; Sarah Little; Catherine Gakii; John Mungai; Cynthia Kahumbura; Sathyanath Rajasekharan; Anneka Wickramanayake; Margaret McConnell; Jessica Cohen (PLOS Global Public Health, 2026)
Maternal and neonatal mortality rates remain high in sub-Saharan Africa despite increased facility-based childbirth, reflecting persistent gaps in quality of care. We evaluated the impact of MENTORS, a facility based nurse mentorship and training program, on provider knowledge and childbirth care quality. In an unblinded parallel-arm cluster randomized controlled trial conducted between November 2021, 40 health facilities in Kenya were randomized to receive continuing medical education lectures, simulation-based drills, and in-facility mentorship to strengthen obstetric and newborn care. Baseline data included facility assessments and provider surveys; endline data included provider surveys, a standardized neonatal resuscitation simulation, and childbirth observations. Primary outcomes included provider knowledge, quality of routine maternity care, and quality of neonatal resuscitation management. All outcomes were assessed at endline. The trial was registered at ClinicalTrials.gov (NCT05110521) and the AEA RCT Registry (0008449). At baseline (November-December 2021), 357 providers were interviewed; at endline (May-August 2022), 376 providers were interviewed and 4,377 childbirths were observed. Routine maternity care quality was low across facilities, with providers performing 58.6% of essential actions in intervention facilities and 57.0% in control facilities at endline. There was no significant difference between the intervention and control facilities in provider knowledge (unadjusted domain effect 0.006, 95% CI: -0.038, 0.051) nor the quality of routine maternity care (0.018, 95% CI: -0.029, 0.065). However, providers in intervention-exposed facilities demonstrated improved quality of neonatal resuscitation in simulation-based assessments (0.094, 95% CI: 0.000, 0.188), with suggestive evidence of improved performance in standardized childbirth observations as well (0.041, 95% CI: -0.001, 0.083). Routine maternity care quality was suboptimal across both intervention and control facilities. While the facility-based mentorship program did not significantly improve provider knowledge or the quality of routine childbirth care, it showed evidence of improvements in neonatal resuscitation, although these findings were not robust across all sensitivity analyses.